Rational and mythological in consciousness of Fyodor Mikhaylovich Dostoyevsky’s hero - Ельницкая, Людмила (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article considers two types of consciousness, which are typical of Dostoyevsky's heroes. The first type searches for support in human mind. However, individualism of the modern person leads him to revolt against the world, and gives rise to solitude and isolation in the "underground". Such rational thinking creates deadly deadlock to the existence of the human. The second type of consciousness is mythological. It is also connected with the inevitability of death which is, however, a condition of the subsequent revival and the rebirth, allowing the person to see the world differently.